1973
DOI: 10.1111/j.1365-2389.1973.tb00772.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mobilization and Fixation of Molybdenum, Vanadium, and Uranium by Decomposing Plant Matter

Abstract: Mo, V, and U are mobilized as anions by aerobically decomposing plant matter; the behaviour of the dissolved metals differs in several respects from what would be expected in inorganic systems.With respect to dialysis through cellophane, between p H I and 4 the mobilized Mo is fixed by colloidal organic decomposition products, with maximum retention at pH 1.5; V is retained between p H 1.5 and 7.0, with a maximum at pH 3.The specific fixation of Mo and V by soil organic matter was considerably less, and persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

1975
1975
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…This is at least 100 times greater than the concentrations recorded in this study. The survey by Arthur et al (1953) showed that in Ontario there are areas where Molybdenum toxicity in field-grown crops has not been observed (Jarell et al 1980 This resulted in increased plant Mo concentrations in some treatments but these are within the 0.1-to 3-mg'kg-t range considered normal by Chaney (1982) Bloomfield and Kelso (1973). This would explain the large increase in uptake of Mo from the Ca-sludge-treated soil in 1980. Other factors may have influenced Mo uptake to some extent thereby causing concentrations in plants to vary somewhat from year to year, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…This is at least 100 times greater than the concentrations recorded in this study. The survey by Arthur et al (1953) showed that in Ontario there are areas where Molybdenum toxicity in field-grown crops has not been observed (Jarell et al 1980 This resulted in increased plant Mo concentrations in some treatments but these are within the 0.1-to 3-mg'kg-t range considered normal by Chaney (1982) Bloomfield and Kelso (1973). This would explain the large increase in uptake of Mo from the Ca-sludge-treated soil in 1980. Other factors may have influenced Mo uptake to some extent thereby causing concentrations in plants to vary somewhat from year to year, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The potential of V to accumulate or be retained by sediments under strongly reducing conditions has been recognised. [10,15] V is also known to be incorporated into enzymes of nitrogenfixing bacteria. [32,33] Bacterial cultures isolated from crude oilcontaminated land have been shown to bioaccumulate vanadium from agar medium at high V concentration.…”
Section: In Situ Profilesmentioning
confidence: 99%
“…Vanadium is likely to be in the measurable form H 2 VO − 4 in the pH range 5-9 and the E h (redox potential) range 0-1 V. [9] Reduction of V V to V IV can occur with organic materials as electron donors, [10,11] with reduction to V III requiring a stronger reductant. V III is rapidly hydrolysed in aqueous solution, resulting in the precipitation of relatively insoluble V III oxyhydroxides.…”
Section: Introductionmentioning
confidence: 99%
“…16f), indiquant une relation plutôt liée à la tourbe qu'à la profondeur même de l'échantillon. Dans le sol, les agents réducteurs comme la MO viennent jouer un rôle important dans le cycle du V. Les mesures de la teneur en vanadium des sols riches en MO et des tourbes ont montré qu'un enrichissement substantiel de cet élément se produit par rapport à l'abondance géochimique moyenne (Bloomfied and Kelso, 1973;Szalay and Szilagyi, 1967 Figure 17 : Mise en plan de la CP2 avec le pôle négatif (points bleu pâle) et le pôle positif (points bleu foncé) sur fond de photographie aérienne. Les coordonnées sont en UTM Nad83, Zone 18.…”
Section: Cp2unclassified